Illegal immigration in Spain and Europe: Situation and outlook - Elena Inglada Galiana; José Manuel Sastre Centeno; Maria Cristina de Miguel Bilbao (Revista Galega de Economía, 2019)
Migration has been a necessary distinctive feature since the dawn of history and there is a universal consensus in recognizing that it has contributed significantly to the progress of societies. In the Spanish society, immigration is one of the current phenomena that has determined the past and future configuration of the country. This has also happened in Europe, where the arrival of foreigners has been a gradual and repetitive phenomenon in virtually every country. However, illegal immigration is associated with exploitation and vulnerability, where the illegal immigrant becomes invisible in the receiving country, which is one of the greatest obstacles that needs to be overcome. The concern about this type of immigration is recent, and it is associated with the border controls and immigration policies of each country. The incidence and its extension in different sectors, such as social or economic, are multiple and heterogeneous. And this is the object of study of this work.